Rotation Impact on On‐Farm Yield and Input‐Use Efficiency in High‐Yield Irrigated Maize–Soybean Systems. (1st November 2016) - Farmaha, Bhupinder S.; Eskridge, Kent M.; Cassman, Kenneth G.; Specht, James E.; Yang, Haishun; Grassini, Patricio
Abstract : Cereal yields tend to be higher in cereal–legume rotations relative to cereal monoculture yields. We investigated the influence of crop rotation on yield and input‐use efficiency in high‐yield irrigated maize ( Zea mays L.)‐based cropping systems using producer‐reported data from western U.S. Corn Belt (about 11, 000 observations). Across regions, average yield of maize grown after soybean [ Glycine max (L.) Merr.] (S–M) was 0.2 to 0.6 Mg ha −1 (2–5%) higher, relative to yield of maize grown after maize (M–M). Soybean yield was 5% greater after two consecutive maize crops (M–M–S) than after only 1 yr of maize (S–M–S). Nitrogen fertilizer rate in maize fields was 13 kg N ha −1 (6%) lower in S–M than M–M fields, which, together with higher maize yields in S–M fields, resulted in 11% higher nitrogen partial factor productivity (PFPN ). Difference in PFPN was unrelated with residual soil N–NO3 − from prior crop. Analysis of rotation data indicated that rotation effect persists across a wide range of maize yields, from 6 to 15 Mg ha −1, though magnitude of rotation effect decreases with increasing yield level. Trends toward greater proportion of total maize area in S–M, rather than M–M, accounts for 8% of maize yield gain in U.S. Corn Belt since 1970. Similarity between our findings and previous research highlights the opportunity to quantify impact of management on yield and efficiencies by using producer data as a complement to high‐cost multi‐year, multi‐site field experiments. Core Ideas We assessed rotation effect on on‐farm yield and input‐use efficiency. Analysis was based on a large producer‐reported database collected from high‐yield irrigated maize–soybean systems. There was a consistent positive rotation effect on yield and partial factor productivity for N fertilizer. Number of previous maize crops did not affect maize yield in monoculture but soybean yields were higher following multiple maize crops. Increasing maize area in rotation relative to monoculture accounts for 8% of the maize yield gain in the U.S. Corn Belt since 1970.